2022
DOI: 10.24272/j.issn.2095-8137.2021.299
|View full text |Cite
|
Sign up to set email alerts
|

Rapid genetic divergence and mitonuclear discordance in the Taliang knobby newt (<i>Liangshantriton taliangensis,</i> Salamandridae, Caudata) and their driving forces

Abstract: The Hengduan Mountains Region (HMR) is the largest “evolutionary frontier” of the northern temperate zone, and the origin and maintenance of species in this area is a research hotspot. Exploring species-specific responses to historical and contemporary environmental changes will improve our understanding of the role of this region in maintaining biodiversity. In this study, mitochondrial and microsatellite diversities were used to assess the contributions of paleogeological events, Pleistocene climatic oscilla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 120 publications
(162 reference statements)
1
3
0
Order By: Relevance
“…Lin et al ( 2021 ) proposed that niche divergence caused by northward niche expansion accompanied key morphological innovations of adaptation to novel climates. Our research showed that IBE contributed to the divergent population structure ( Figure 7B , C), as reported for the Taliang knobby newt ( Liangshantriton taliangensis , Shu et al, 2022 ), suggesting that gene flow rates are higher among similar environments and environmental variables can influence colonization success of individuals and groups via environmental filtering, with higher effective gene movement among similar environments ( García-Girón et al, 2019 ; Sexton et al, 2014 ).…”
Section: Discussionsupporting
confidence: 76%
“…Lin et al ( 2021 ) proposed that niche divergence caused by northward niche expansion accompanied key morphological innovations of adaptation to novel climates. Our research showed that IBE contributed to the divergent population structure ( Figure 7B , C), as reported for the Taliang knobby newt ( Liangshantriton taliangensis , Shu et al, 2022 ), suggesting that gene flow rates are higher among similar environments and environmental variables can influence colonization success of individuals and groups via environmental filtering, with higher effective gene movement among similar environments ( García-Girón et al, 2019 ; Sexton et al, 2014 ).…”
Section: Discussionsupporting
confidence: 76%
“…Resistance distance calculations in IBR often utilize data related to species traits or habitats ( Thomas et al 2015 ; Weber et al 2017 ). One common method is to calculate resistance distance based on niche model predictions, since gene flow between populations can be limited by suitable habitats ( Myers et al 2019 ; Zhang et al 2020 ; Shu et al 2022 ; Moreno-Contreras et al 2023 ). In IBE and IBR analyses, based on L. lutea 's elevational distribution range and preference for evergreen broadleaved forest and woodland, we considered 2 other variables in addition to the bioclimatic factors, namely altitude and land cover.…”
Section: Discussionmentioning
confidence: 99%
“… 34 Post-glacial population expansions after LGM and LGP have been inferred for many vertebrate groups, 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 including Eurasian salamandrids from similar latitudes. 43 , 44 , 45 However, well documented post-glacial bottlenecks are scarcer in the genomic literature and typically limited to either relict or extinct megafauna. 37 , 46 , 47 , 48 , 49 Although paleodemographic modeling has statistically shown tight links between demography and climate oscillations for humans at the end of LGP from archaeological radiocarbon dates, 39 , 50 to our knowledge this is the first time the dependence of a genomically inferred past demography on climate variables is proven, moreover, on a non-model species.…”
Section: Discussionmentioning
confidence: 99%